Current climate overrides historical effects on species richness and range size of freshwater plants in Europe and North America. (13th February 2020) - Alahuhta, Janne; Antikainen, Harri; Hjort, Jan; Helm, Aveliina; Heino, Jani
Abstract: The latitudinal diversity gradient hypothesis suggests that species richness should be highest at low latitudes, whereas Rapoport's rule states that largest ranges ought to be found for species at high latitudes. However, there is no consensus over these patterns and their underlying drivers in the freshwater realm. We investigated species richness and mean range size of freshwater plants in 50 × 50 km grid cells across Europe (40°N–71°N) and North America (25°N–78°N), supplemented with data based on 1° latitudinal bands for mean range size. We were especially interested to find out whether there are similarities and differences in these ecogeographical patterns and their underlying drivers between the continents due to their contrasting historical characteristics, spatial extent and topography. First, we used partial regression to reveal whether species richness and mean range size of freshwater plants have a linear or quadratic relationship with latitude. Second, we employed variation partitioning based on partial regression to model relationships between plant species richness and mean range size and four explanatory variable groups (i.e. environmental features, current climate, historical climate and geographical location). Third, we utilized boosted regression tree analysis to further investigate species richness and mean range size of freshwater plants in relation to a set of explanatory variables. Our results revealed that species richness showed relatively similar patterns in relation to latitude between the continents. Similarly, mean range size trends were alike in North America whether we used 50 × 50 km grid cell data or 1° latitudinal bands. Instead, different patterns in mean range size emerged between the used datasets in Europe. For both species richness and mean range size, current climate (with different individual predictor variables) was the main driver in both the continents, but historical effects had a small influence on the response variables. Synthesis . Our findings indicated that major ecogeographical rules can strongly vary for the same taxonomic group across broad scales between continents. It is also premature to rely solely on well‐known terrestrial taxonomic groups when drawing generalizations about ecogeographical rules. Abstract : Our findings indicated that major ecogeographical rules can strongly vary for the same taxonomic group across broad scales between continents. It is also premature to rely solely on well‐known terrestrial taxonomic groups when drawing generalizations about ecogeographical rules.